PENENTUAN DAERAH PROSPEK MINERALISASI MENGGUNAKAN METODE GEOKIMIA TANAH, DAERAH NANGA BANGIK, KECAMATAN BOYAN TANJUNG, KABUPATEN KAPUAS HULU, PROVINSI KALIMANTAN BARAT: DETERMINATION OF MINERALIZATION PROSPECTS BY SOIL GEOCHEMISTRY METHOD IN NANGA BANGIK AREA, BOYAN TANJUNG DISTRICT, KAPUAS HULU REGENCY, WEST KALIMANTAN PROVINCE - Sulaeman; Ernowo; Widhiyatna, Denni (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2021)
The tropical climate of Indonesia causes rock weathering. Soil from weathered rocks can be analyzed to determine the anomalies element to define the mineralization prospect areas using the geochemical methods. This study was carried out in the Nanga Bangik area with geological conditions favorable for mineralization. A total of 135 soil samples were collected from horizon B along ridge and spurs with sample intervals 75 - 100 meters. All samples were analyzed at the laboratory of the Center for Mineral Coal and Geothermal Resources in Bandung. Geochemical analysis was conducted using the Atomic Absorption Spectroscopy method, for the elements of Cu, Pb, Zn, Fe, Mn, Ag, and Au. Statistical distribution analysis, threshold calculation using mean+2SDEV and Median+2MAD and correlation between Factor Analysis were combined to determine the anomalies areas. Based on the calculation of the threshold using two different statistical methods, several anomalous values and groups of three factors were obtained: Factor 1: Pb-Fe-Zn-Ag Factor 2: Mn-Cu and Factor 3 in the form of element Au which was interpreted by the presence of metal mineralization. Three mineralization prospect areas were found in Bukit Empajak, Bukit Pirang and Bukit Limau.